2015
DOI: 10.1007/s00520-015-2957-5
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting classification of pain from bone metastases as mild, moderate, or severe based on correlation with function and quality of life

Abstract: Purpose The objective of our study was to determine the optimal cut points for classification of pain scores as mild, moderate, and severe based on interference with function and quality of life (QOL). Methods We evaluated 822 patients who completed the Brief Pain Inventory (BPI) and/or the European Organization for Research and Treatment of Cancer (EORTC) QOL Questionnaire Core 30 (QLQ-C30) prior to receiving repeat radiation therapy for previously irradiated painful bone metastases. Optimal cut points for mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Investigations have also used anchor-based methods to describe grades of symptom severity as the basis for establishing cutpoints between mild, moderate, and severe levels for various symptoms [43].…”
Section: Discussionmentioning
confidence: 99%
“…Investigations have also used anchor-based methods to describe grades of symptom severity as the basis for establishing cutpoints between mild, moderate, and severe levels for various symptoms [43].…”
Section: Discussionmentioning
confidence: 99%
“…Pain scores are classified as follows: VAS 1-4, mild pain; 5-8, moderate pain; and 9-10 as severe pain ( 43 ). Previous studies of osteoblastic spinal metastases showed postoperative pain relief.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals answered the 12‐Item Short Form (SF‐12) questionnaire item “pain limits normal work” ([1] not at all [ n = 1,328], [2] a little bit [ n = 1,579], [3] moderately [ n = 1,097], [4] quite a bit [ n = 1,184], and [5] extremely [ n = 533]). Based on research relating pain levels to quality of life, a 3‐category model provided good discriminative fit (1 to 2 as mild, 3 to 4 as moderate, and 5 as severe). We further collapsed the response categories into dichotomous coding to reduce the false‐positive rate and to maximize the ability to distinguish low‐ or no‐pain conditions from pain‐related reports.…”
Section: Methodsmentioning
confidence: 99%